Production and employment impacts of new technologies: analysis for biotechnology - Sven Wydra (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2009)
Biotechnology is often regarded as a key technology with high potential for far-reaching social, environmental and economic impacts. Among others, the development and diffusion of biotechnology may have considerable economic effects on production and employment. This paper analyzes the economic impacts of different diffusion paths of biotechnology in some major application fields. Bottom-up technology information from literature, expert judgements and explicit scenario assumptions for various impact factors are combined and integrated in an input-output framework to calculate direct and indirect production and employment effects. The impact on net production and employment differs greatly between the different application sectors and depends on the respective importance of the various impact mechanisms. The indirect economic effects are rather high and exceed direct economic effects. These findings show the importance of a bottom-up approach as well as the consideration of indirect economic effects for appropriate analyses of the impact of biotechnology.
urn:nbn:de:bsz:100-opus-3971
Keywords: C67; O14; O33; J23; 330; Economic impacts of technologies; employment effects; input-output model; biotechnology; Biotechnologie; Innovationsdiffusion; Input-Output; Beschäftigungseffekt; OECD-Staaten